(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
An experiment was conducted at the research field in the Department of Agriculture, Noakhali Science and Technology University, Noakhali, Bangladesh during the period from March to July 2022 to study the effect of vermicompost on growth and yield of okra. The experiment was laid out in a Randomized Complete Block Design (RCBD) comprising four treatments with three replications. The four treatments were T0 (Control), T1 (Vermicompost 10 t ha-1), T2 (Vermicompost 15 t ha-1) and T3 (Vermicompost 20 t ha-1). Green finger F1 okra used as planting material. Data were recorded from different stages of plant growth viz, plant height, days of flowering, fruit per plant, fruit length, fruit diameter, fruit weight, fruit weight per plant, yield per plot and yield per hectare. All the recorded parameters were statistically significant (P<0.01). The maximum days to first flowering (47.31 days) was recorded from T0 (Control), while the minimum days for first flowering (40.67 days) was found from treatment T3 (Vermicompost 20 t ha-1). The maximum height of okra plant (100.43 cm), number of fruits per plant (22.13), fruit length (13.60 cm), fruit diameter (2.01 cm), fruit weight (13.47 g), fruit weight per plant (198.02 g), yield per plot (1.78 kg), yield per hectare (17.8 t ha-1) were found in treatment T3 (Vermicompost 20 t ha-1) whereas lowest data recorded in treatment T0 (Control). Observing the results, it can be stated that application of vermicompost @ 20 t ha-1 for okra cultivation gave better growth and yield in the coastal area of Bangladesh. Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 165-173